2021
DOI: 10.1016/j.idcr.2021.e01071
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus-associated vasculitis: A role for antibiotic therapy?

Abstract: Numerous post-Streptococcal syndromes (PSS) have been described in the literature. The role of antibiotic therapy in the management of PSS is best established with acute rheumatic fever. We present a patient with streptococcus-associated medium vessel vasculitis with multiple flares despite immunosuppressive therapy that achieved a sustained remission with long term oral penicillin V 250 mg twice daily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Here, we found that EGPA patients receiving systemic immunosuppressants had significantly lower levels of Enterobacteriaceae compared to non-immunosuppressed patients. These findings, while suggesting a potential association between these bacteria and the systemic inflammatory state, support also the hypothesis that an appropriate treatment of vasculitis could reshape the microbiota composition towards a healthier profile [ 41 ].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Here, we found that EGPA patients receiving systemic immunosuppressants had significantly lower levels of Enterobacteriaceae compared to non-immunosuppressed patients. These findings, while suggesting a potential association between these bacteria and the systemic inflammatory state, support also the hypothesis that an appropriate treatment of vasculitis could reshape the microbiota composition towards a healthier profile [ 41 ].…”
Section: Discussionsupporting
confidence: 69%
“…Another distinctive feature of EGPA was the enrichment in Streptococcaceae, particularly in subjects with active disease. Interestingly, this family includes Streptococcus spp., which is responsible for streptococcus-associated medium-vessel vasculitis [ 41 ], and that has been found increased in faecal samples of patients with active Kawasaki disease [ 42 ], a systemic small- to medium-sized-vessel vasculitis. Nevertheless, the specific mechanisms underlying the association between Streptococcaceae abundance and active EGPA remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Streptococcus is another major group of common Gram-positive cocci in pyogenic cocci. There are 69 species and subspecies, which are widely distributed in nature and the nasopharynx, gastrointestinal tract of the human body, and most of them belong to normal genus (158). Pathogenic Streptococci can cause a variety of purulent inflammation and hypersensitivity diseases in humans, among which group B Streptococcus (GBS) are the most threatening to infants (159).…”
Section: The Genus Veillonella and Streptococcusmentioning
confidence: 99%